SOBRE SER, PENSAMENTO E DISCURSO NO POEMA DE PARMÊNIDES - Soares (PUCRS/UPF), Marcio (Intuitio, 2008)
ABSTRACT: We aim to address the relationships between to be, to think and to say in the philosophy of Parmenides of Elea. In that sense, we try to demonstrate the systematic imbrication between those three dimensions, as long as, according to the Eleatic Philosopher, just what really is (the being) can be said and thought as a safe path of philosophical investigation. Our purpose is also to demonstrate that the is not ends up representing just a linguistic expression, purely negative in the Parmenidian philosophy, without any real (ontic) correspondence. With this, we want to defend that the path of non-being and the opinions of mortal men are different and must not be confused. From this interpretative proposition of the poem by Parmenides, we speculate the limits and paradoxes of his philosophy, thinking the non-being as a negative expression in language, at the same time that the Philosopher completely forbids its investigation. We also seek, at the final part of the text, to discuss the concept of discourse that results from Parmenidian philosophy, especially related to opinion. For such, we begin by analyzing the proem of the Parmenidian poem from the perspective of Greek poetic tradition, trying to demonstrate that our Philosopher lies in a border region between poetry and rising philosophy. KEY WORDS: Goddess. Being. Non-being. Appearance. Opinion. Discourse. Thought. Philosophical discourse.